PENGARUH CONSUMER ETHNOCENTRISM TERHADAP COUNTRY OF ORIGIN DAN PURCHASE INTENTION KOSMETIK LOKAL DI DENPASAR - Ni Putu Anggun Udayani; Made Wardana; IG.A.K. Giantari (JUIMA : JURNAL ILMU MANAJEMEN, 2018)
There is intense competition between local and foreign cosmetic industry in Indonesia. Imported cosmetics dominate the business market by 80%, while only 20% for local cosmetics. Theconceptof consumen ethnocentrismand country of originis considered as one way to help the local cosmetic industry to face competition from imported cosmetics. The purpose of this study is to determine 1) Theeffectof demographic characteristics (age, income, education) to consumer ethnocentrism; 2) Theeffectof consumer ethnocentrismand countryof origin to the consumer purchase intentions; 3) The influence of country of originas a mediation of consumer ethnocentrism and purchase intention. The samples used were 125 cosmetic users who live in Denpasar City taken by purposive sampling method. The analysis technique use dis the One Way ANOVA and PLS (Partial Least Square).,The results showed that 1) Consumer demographic of age and income showed a significant effect to distinguish consumer ethnocentrism, while education did not have a significant influence on consumer ethnocentrism; 2) Consumer ethnocentrism and country of originhasa positive significant effect towards the purchase intention of local cosmetics; 3) Recently, country of origin partially media tes the effect of consumer ethnocentrism on purchase intention. This finding simplicates that purchase intention of local cosmetics is influenced by consum erthnocentrism and country of origin. Management need more concern to use those factors to develop marketing communication and improve the product quality.